Forestry meets Steel. A Technoeconomic study of the possible DRI production using biomass - Grip, Carl-Erik; Toffolo, Andrea; Salman, Hassan; Andersson, Lars I.; Ritzen, Ola; Tottie, Magnus; Robinnsson, Ryan; Winnikka, Henrik; Östman, Marianne; Sandberg, Erik (Luleå tekniska universitet, Energivetenskap, 2015)
The possibility to produce DRI using gasified Biomass is studied in a cooperative project. LTU, MEFOS, ETC and five industries in the areas forestry & pulp, mining, iron and gas are involved. The production chain Biomass production and distribution -Gasification-DRI production-DRI use is investigated in four work packages:WP1: Biomass supply: A large amount of Biomass has to be delivered into a single site to exchange a large amount of fossil reductant. It is important to use forestry by- products as a major part of round wood is reserved for other uses. Harvesting, logistics and economics have to be considered. Available data were collected and used to make a system model on harvesting treatment and transport. The simulations indicated that the supply of residuals is possible but will need material from a large part of the north Sweden wood area. WP2: Gasification. The aim is to use to produce hot gas that can be used directly. Pilot experiments are carried out using oxygen in an entrained flow gasifier. WP3: Metallurgical processes. Reduction tests are carried out with gas that can be produced in the gasifier. The limitations of the gas content are studied as well as the effect on DRI. Also the suitability of the DRI product is evaluated WP4: Process integration. A system model is built using the results from work packages 1-3 and used for technical economic optimization the whole system harvesting-transport-gasifier-direct reduction- use of DRI. The process chain is technically possible; however there are problems to be solved, e.g., gas quality vs. demands from DRI process, Biomass supply and logistics. The result is important to evaluate for industrial application, but also to get information of the effect of different governmental control instruments. Godkänd; 2015; 20150811 (cargri)